Integration of Local Cultural Values in Pencak Silat Learning to Form the Character and Sportsmanship of Elementary School Students - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to analyze the effectiveness of pencak silat learning based on local Makassar cultural values ??in improving the character and sportsmanship of students at Sudirman I Elementary School, Makassar. Twenty students served as the sample, using a one-group pretest-posttest design. The research instrument consisted of a character and sportsmanship questionnaire administered before and after the intervention. Pencak silat learning was designed to integrate Makassar cultural values ??such as sipakatau, sipakainge, and sipakalebbi into each training session. Data were analyzed using descriptive and inferential statistics (paired t-test). The results showed a significant improvement in both study variables. The average character score increased from 72 to 85 (18.05%), while the sportsmanship score increased from 70 to 88 (25.71%). The t-test results showed a p-value of 0.000, indicating a significant difference between the pretest and posttest. The effect size values ??showed a significant influence (d = 1.39 for character and d = 1.78 for sportsmanship), confirming that cultural values-based learning has a strong impact on student behavior. These findings indicate that integrating local culture into pencak silat learning not only improves students' skills and fitness but also strengthens character education in line with the Merdeka Curriculum. This learning model is worthy of recommendation for widespread implementation in elementary school physical education.